Antibody Fc Engineering: Towards Better Therapeutics - Rui Gong (Frontiers Research Topics, 2018)
Monoclonal antibodies and Fc-fusion proteins used clinically are Fc-based therapeutics that grow fastest in the pharmaceutical industry. Since they both contain an Fc fragment, engineering of Fc fragments could be a platform for improving Fc-based drug efficacy. Fc engineering includes various aspects: stabilization of Fc; regulation of effector functions including antibody-dependent cell-mediated cytotoxicity, complement-dependent cytotoxicity; extension of serum half-life by modification of neonatal Fc receptor (FcRn) binding; monomerization or heterodimerization of Fc for design of new Fc formats. Currently, many new methods are being used in Fc engineering. Compared to traditional methods such as site mutagenesis on certain positions by amino acid replacement, new methods such as display-based technology can confer high throughput screening and obtain optimized variants relatively quickly, accelerating the drug development process. With the new methods, many new Fc variants were identified. On this Research Topic we are going to review the progress in current Fc engineering including the new engineering methods and the Fc variants or constructs they have produced, and the potential of these new Fcs in clinical use.